Carinata Production in Florida - C. M. Bliss; Ramdeo Seepaul; David L. Wright; James J. Marois; Ramon Leon; Nicholas Dufault; Sheeja George; Stephen M. Olson (EDIS)
Brassica carinata is a promising oilseed crop with great potential for profitable cultivation in Florida. Its high oil content and favorable fatty acid profile make it suitable for the biofuel industry, especially as a biojet fuel. The UF/IFAS North Florida Research and Education Center (NFREC) in Quincy, Florida, has been working to identify advanced carinata genotypes that are high yielding (seed and oil), disease resistant, early maturing, and adapted to Florida. The work at NFREC is being done in conjunction with Agrisoma Biosciences Inc., a crop company that has the world’s largest collection of carinata germplasm. This 6-page fact sheet’s “Agronomic Management” section provides recommendations resulting from NFREC’s research. It was written by C. M. Bliss, R. Seepaul, D. L. Wright, J. J. Marois, R. Leon, N. Dufault, S. George, and S. M. Olson, and published by the UF Department of Agronomy, December 2014.